2014
DOI: 10.1002/jcp.24497
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-200b Stimulates Tumour Growth in TGFBR2-Null Colorectal Cancers by Negatively Regulating p27/kip1

Abstract: Colorectal cancer (CRC) remains the most common malignancy worldwide. TGF-β1 is often overexpressed in late stages of colorectal carcinogenesis and promotes tumour growth and metastasis. Several reports have verified that the loss of functional TGFBRII expression contributed to escape the tumour suppressor activity of TGF-β1 and that the epithelial-to-mesenchymal transition (EMT) responded to TGF-β1 involved in tumour invasion and metastasis. However, the mechanisms by which TGF-β1 confers a growth advantage t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
24
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(25 citation statements)
references
References 42 publications
(59 reference statements)
1
24
0
Order By: Relevance
“…Interestingly, the authors demonstrated increased SIX1 expression at the invasive border of clinical samples, which highlights the role that it may have in EMT modulation. 32 This interesting dichotomous role for the miR-200 family may be mediated by TGFBRII expression. While the miR-200 family is classically described in the ZEB1/E-cadherin pathway, there is an interesting differential expression noted between TGFBRII-expressive and deficient CRC cell lines.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, the authors demonstrated increased SIX1 expression at the invasive border of clinical samples, which highlights the role that it may have in EMT modulation. 32 This interesting dichotomous role for the miR-200 family may be mediated by TGFBRII expression. While the miR-200 family is classically described in the ZEB1/E-cadherin pathway, there is an interesting differential expression noted between TGFBRII-expressive and deficient CRC cell lines.…”
Section: Resultsmentioning
confidence: 99%
“…31 Conversely, TGF-b1 induces cellular proliferation in TGFBRII-deficient cell lines, with associated increased miR-200b. 32 This interesting dichotomous role for the miR-200 family may be mediated by TGFBRII expression. KRAS is a well described oncogene, which has been implicated in colorectal carcinogenesis.…”
Section: Other Pathwaysmentioning
confidence: 99%
“…Diminished numbers of iNKT cells in peripheral blood lymphocytes were found in persons with autoimmune diseases such as RA, systemic lupus erythematosus, systemic sclerosis, and Sjogren's syndrome (29). Therefore, miR-150 might (30). Tamoxifen inhibits miR-200 expression and promotes epithelial-to-mesenchymal transition by upregulating c-Myc in endometrial cancer cells (31).…”
Section: Discussionmentioning
confidence: 99%
“…As a consequence, cyclin D1, a downstream target of RND3, was increased along with S-phase entry (143). The association between miR-200b and RND3 could be extended to colorectal carcinoma (39) and human Tenon’s capsule fibroblasts (HTFs) (130). Using the informatics and qRT-PCR approach, Hurteau et al identified that Rnd3 may also be a target of miR-200c (58).…”
Section: Rnd3 Regulationmentioning
confidence: 99%